Kaunseling Dakwah: Suatu Pengenalan Konsep - Mohd Zin, Ab. Aziz; Md. Yusoff, Yusmini binti (Jurnal Usuluddin, 2001)
The article discusses counseling for da'wah particularly the implementation of da'wah basic concepts in counseling process such as helping relation ships, muhasabah or improving the clients ability to understand and clarify their views of their life space and facilitating behave or change.